Faktor-Faktor yang Berhubungan dengan Penggunaan Kontrasepsi Pil di Wilayah Kerja Balai Penyuluh KB Kecamatan Jejangkit Tahun 2022 - Fatma Amelia; Norfai Norfai; Mahmudah Mahmudah; Eddy Rahman (Jurnal Akademika Baiturrahim Jambi, 2023)
Pil KB a hormonal contraceptives that aim to prevent the occurrence of pregnancy that is added to a woman’s body by taking (pills) the purpose of taking birth control pills regularly is to prevent, inhibit the occurrence of unwanted pregnancies. This study aims to analyze factors related to the use of contraceptive pills in the Working Area of the Jejangkit district KB Extension Center in 2022. This type of research is quantitative using a cross sectional approach. The sample size of 83 active KB participants was taken using the proportional random sampling technique. Data collection in this study used questionnaires. Based on the chi square statistical test, bivariate test results found that there was a significant relationship between maternal knowledge (p-value = 0.000), attitude (p-value = 0.012), husband support (p-value = 0.000) and the use of pill contraceptives in the Working Area of balai penyuluh KB district Jejangkit in 2022. There is on significant relationship between education level (p-value = 0.431) and parity (p-value = 0.100) with the use of pill contraceptives in the working area of balai penyuluh KB district Jejangkit in 2022. It is necessary to carry out intensive education, efforts to monitor and evaluate the campliance of the community to use cantraceptive pills to the more optimal and for mothers to be more disciplined using contraceptive pills.